Little evidence for color- or size-based mating preferences by male strawberry poison frogs (Oophaga pumilio) - Mik R. Lehman; Marco González-Santoro; Corinne L. Richards-Zawacki (Behavioral Ecology and Sociobiology, 2024)
While there are many studies documenting female mating preferences across taxa, male mate choice remains relatively understudied. Male mate choice often develops when there is variation in female quality and thus the fitness benefits of mating with particular females. Specifically, males tend to prefer females with traits that confer direct fitness benefits such as large body size, which may be linked with high fecundity. Prior work has shown that females of the strawberry poison frog, Oophaga pumilio , prefer males bearing certain coloration (most often the female’s own color), and that this preference can be learned through maternal imprinting. Females have been shown to prefer larger males as well. Here we test whether similar mate preferences for color and size exist in males of this species using two-way choice tests on captive bred male O. pumilio . In each test focal males were placed in an arena with two stimulus females: either both of the same size but differing in color, or both of the same color but differing in size. We found only weak evidence for behavioral biases toward particular colors and no evidence for biases toward larger females, suggesting that males of O. pumilio do not predictably choose mates based on these female traits. Despite several aspects of their natural history that suggest males have reasons to be choosy, our findings suggest that the cost of mate rejection may outweigh any fitness benefits derived from being selective of mates. Studies of additional populations, ideally conducted on wild individuals, are needed to better understand the range of conditions under which males may exhibit mate choice and the types of traits on which they base these choices. Significance statement To fully understand the fitness landscapes and evolutionary trajectories that result from sexual selection, we need to understand when and how the mate preferences of the two sexes act and interact. While female mate choice has been widely studied, male mate choice remains poorly understood. To help bridge this gap, we studied male mate preferences in the strawberry poison frog Oophaga pumilio , a small brightly colored frog for which female preferences for male color and size have been well-documented. We found no evidence that male O. pumilio exhibit mate preferences based on female size and little evidence for male mate preferences based on female color. This is surprising given that larger females are often more fecund, male O. pumilio are known to exhibit color-based behavioral biases in the context of male-male competition, and both sexes provide parental care.